Enhancement of mechanical properties of lightweight concrete - Husain, Mohamed; A Khater, Mohamed; El-Ghamry, Asmaa (International Journal of Engineering and Technology, 2019)
In this presented paper, Three concrete mixtures were set to produce a Lightweight Aggregate Concrete (LWAC) using Expanded perlite aggregate (EPA) as a replacement of natural gravel. EPA used with replacement fractions of 0%, 30%, and 40% by weight of the coarse aggregate. An additional eight concrete mixtures were arranged to study the influence of using steel fiber (SF) and polypropylene fiber (PP) with various percentages on the mechanical properties of samples with 30% and 40% perlite content. The volumetric ratios of SF and PP fiber were 0%, .5%, 1%. The main objectives of this paper are to produce perlite concrete with a density less than 2000 kg/m3 and with 28-days cube compressive strength not less than 18 MPa, also to enhance perlite concrete properties with two types of fibers. The mechanical properties measured in this experimental work are composed of 28-day cube compressive strength, unit weight, flexural strength, and splitting-tensile strength. From the gained data, the required reduction in unit weight values of perlite concrete has been achieved. Also, steel fibers improved the tensile properties of perlite concrete more than PP fibers.